Implementation and Impact of Servant Leadership in Various Contexts: Education, Organisations, Government, and Culture - Andi Indriani Ibrahim; Syahbudin Adam; Selvi; Misra A Gundu; Sulis A Unggu; Yunifa Keleng; Rahmat M Bungu (Universitas Muhammadiyah Palu, 2025)
Servant Leadership is a leadership approach that places leaders as servants for individuals and groups, with a focus on empowerment, empathy, and devotion. Its implementation in various contexts shows positive results, both in the fields of education, organization, government, and culture. In education, servnt leadership encourages the creation of an inclusive and collaborative learning environment, while in organizations, this model increases the satisfaction, loyalty, and employee productivity. In the realm of government, Servant Leadership plays a role in building governance with integrity, increasing public confidence, and strengthening community participation. Meanwhile, from a cultural perspective, this leadership practice is adaptive because it can be adjusted to the local value of the community. Thus, Servant Leadership not only has a positive impact on the performance of individuals and institutions, but also strengthens sustainable social relations in various sectors of life.